From Geoheritage to Geoparks Case Studies from Africa and Beyond - Errami, Ezzoura; Brocx, Margaret; Semeniuk, Vic (Geoheritage, Geoparks and Geotourism, Conservation and Management Series, 2015)
This unique book is dedicated to helping promote geoheritage, geoconservation, and geoparks in Africa and the Middle East. Local, regional, global and thematic case studies including a geoheritage toolkit are used to illustrate the scope and depth of geoheritage and highlight some current geoparks and aspiring candidates in Africa, the Middle East, China , Europe,and Australia. This special issue mainly consists of the proceedings of the First International Conference on Geoparks in Africa and Middle East (FICGAME) held in, El Jadida, Morocco in 2011. The conference, hosted by the Faculty of Sciences of Chouaib Doukkali University, was organized by the African Geoparks Network and the African Association of Women in Geosciences incollaboration with the UNESCO Cairo Office.